2020
DOI: 10.3389/fnut.2020.537049
|View full text |Cite
|
Sign up to set email alerts
|

Preference for High Dietary Salt Intake Is Associated With Undiagnosed Type 2 Diabetes: The Henan Rural Cohort

Abstract: Background: Diabetes continues to be a serious disease burden globally. Nutrition plays a vital role in human life and health, and both inadequate and over nutrition have been implicated in cause the of disease. Objective: We explored the role of preference for high dietary salt intake and diabetes in a rural population. We also looked at possible mediating factors in the relationship between diabetes and preference for high dietary salt intake. Methods/Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Despite the lack of clarity on the pathophysiological connection between sodium intake and diabetes, several potential mechanisms could explain the association. Some studies have attributed the link to excess salt intake associated with increased consumption of sugar-containing beverages, obesity and high blood pressure, which are both risk factors for diabetes ( 18 , 35 37 ), moreover, in diabetic animal models, a high-salt diet aggravated renal fibrosis and impaired fatty acid metabolism ( 38 ). However, our study excluded people with high blood pressure and adjusted for BMI, and the association remained.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of clarity on the pathophysiological connection between sodium intake and diabetes, several potential mechanisms could explain the association. Some studies have attributed the link to excess salt intake associated with increased consumption of sugar-containing beverages, obesity and high blood pressure, which are both risk factors for diabetes ( 18 , 35 37 ), moreover, in diabetic animal models, a high-salt diet aggravated renal fibrosis and impaired fatty acid metabolism ( 38 ). However, our study excluded people with high blood pressure and adjusted for BMI, and the association remained.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study in Finland reported that the relationship between sodium intake and risk of T2DM based on 24-h urinary sodium excretion data showed that high levels of sodium intake, measured in the highest quartile of 24-h sodium excretion, significantly increased the risk of T2DM [ 45 ]. In a recent study by Abdulai et al on the role of a high dietary salt intake preference and diabetes in a rural population in China, the preference for a higher intake of dietary salt was associated with undiagnosed diabetes but not prevalent diabetes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have demonstrated that an excessive salt intake may increase the risk of developing T2DM, possibly through a direct effect on insulin resistance and/or by promoting high blood pressure and weight gain [ 46 , 47 ]. The following presumed mechanisms have been proposed for the association between salt intake and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that excessive consumption of salt can increase the risk of hypertension and existing cardiovascular disease [4,5]. Increasing salt intake also contributes to an increased risk of metabolic disorders like obesity [6][7][8][9], insulin resistance (IR) [10], type 2 diabetes (T2DM) [11,12], metabolic syndrome (MetS) [13,14], and sarcopenia [15]. In light of this, it is meaningful to understand how excessive intake of salt contributes to these health conditions.…”
Section: Introductionmentioning
confidence: 99%